2019
DOI: 10.1016/j.stemcr.2019.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Progression Inhibits Pluripotency and Differentiation of Melanoma-Derived iPSCs Produces Cells with Neural-like Mixed Dysplastic Phenotype

Abstract: Summary Melanomas are known to exhibit phenotypic plasticity. However, the role cellular plasticity plays in melanoma tumor progression and drug resistance is not fully understood. Here, we used reprogramming of melanocytes and melanoma cells to induced pluripotent stem cell (iPSCs) to investigate the relationship between cellular plasticity and melanoma progression and mitogen-activated protein kinase (MAPK) inhibitor resistance. We found that melanocyte reprogramming is prevented by the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Lentiviruses were prepared as described previously [ 48 ]. Briefly, HEK293 cells were plated on 10 cm plates in DMEM and 10% FBS without antibiotics and allowed to reach a 90% confluence within 24–48 h. Following the use of a Lipofectamine 2000 (Thermo Fisher, Waltham, MA, USA, #11668019), the protocol cells were then triple co-transfected with plasmids containing the packaging (psPAX2, Addgene #12260) and a VSV G envelope (pMD2.G, Addgene #12259, Watertown, MA, USA) as well as the target genes BRAF V600E -GFP (a gift from Dr. Raabe [ 49 ]) or empty vector-GFP (a gift from Dr. Herlyn [ 50 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Lentiviruses were prepared as described previously [ 48 ]. Briefly, HEK293 cells were plated on 10 cm plates in DMEM and 10% FBS without antibiotics and allowed to reach a 90% confluence within 24–48 h. Following the use of a Lipofectamine 2000 (Thermo Fisher, Waltham, MA, USA, #11668019), the protocol cells were then triple co-transfected with plasmids containing the packaging (psPAX2, Addgene #12260) and a VSV G envelope (pMD2.G, Addgene #12259, Watertown, MA, USA) as well as the target genes BRAF V600E -GFP (a gift from Dr. Raabe [ 49 ]) or empty vector-GFP (a gift from Dr. Herlyn [ 50 ]).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study aimed at understanding the relationship between melanoma plasticity and MAPKi resistance, we performed whole transcriptome sequence (RNAseq) analysis of MAPKi-sensitive and MAPKi-resistant (both intrinsic and acquired) melanoma cell lines [14].…”
Section: Gene Expression Signatures Of Drug Resistant Melanoma Cellsmentioning
confidence: 99%
“…Recently, using a strategy of reprogramming human melanoma cells to induced-pluripotent cell (iPSC)-like state, we showed that melanoma-derived iPSC-like cells tend to differentiate along mixed-melanocytic and neural-cell lineages, both in vitro and in vivo. These differentiated/transdifferentiated cells also exhibit MAPKi resistance [14] suggesting a relationship between signaling pathways that control transdifferentiation and MAPKi-resistance. This notion is supported by the observation that transdifferentiation to neuroendocrine phenotype correlates with treatment resistance in prostate and lung cancers [5,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hiPSCs, they retain the genetic background of the donor [ 363 ]. Both hiPSCs and hESCs have allowed the study of human cells which are not normally accessible to study in the human body (for example, neurons and glial cells of the human CNS) and, therefore, have boosted the possibilities in medical research employing human cell lines, permitting the study of mechanisms of human development [ 363 , 364 ]; in vitro disease modelling, including in cancer research [ 365 , 366 , 367 ]; in the development of assays and platforms for drug screening campaigns [ 355 , 368 , 369 ]; in patient stratification and in the development of cell replacement strategies [ 355 , 363 ]. The pioneer monolayer cultures gave way to organoids, spheroids, organ-on-a-chip approaches and more recently assembloids, which employ single cell types or a multitude of different cellular types [ 355 , 360 , 370 , 371 , 372 , 373 ].…”
Section: Current Challenges and Future Perspectives In Uveal Melanomamentioning
confidence: 99%